War and peace in the Chittagong Hill Tracts : retrospect and prospect - Hosena, Saiẏada Ānoẏāra, 1934- (Dhaka : Agamee Prakashani, 1999)
Chiefly on insurgency problems in Bangladesh.
Includes bibliographical references.
Keywords: Insurgency -- Bangladesh -- Chittagong Hill Tracts (Region)